EFL LEARNERS’ PERCEPTION OF GRAMMAR NAZIS PRACTICE ON SOCIAL MEDIA TWITTER - Retno Ayu Fitriani; Erna Iftanti (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
This article reviews the EFL perception toward the practices of Grammar Nazi on social media Twitter by outlining the recent activities of Grammar Nazi and the future effect that may use for learning strategy. It aims to discover whether or not the practices of Grammar Nazis have an impact on learners’ desire in learning English. It discusses the EFL learners’ knowledge about the Grammar nazis phenomenon on social media, their perception toward the phenomenon, and the impact of Grammar Nazis on learners’ learning interest. This article indicates that the EFL learners’ have a different perception, on one hand, it motivates their learning desire, and on other hand, it demotivated their interest in learning the language. Based on the review, the article also provides some recommendations on what future researchers can do to explore more about this phenomenon and to use the phenomenon as a learning strategy in improving their English skills.